Influences of specialty identity when implementing a new emergency department in Denmark: a qualitative study - Jeanette Wassar Kirk; Mette Bendtz Lindstroem; Nina Thórný Stefánsdóttir; Ove Andersen; Byron J. Powell; Per Nilsen; Tine Tjørnhøj-Thomsen (BMC, 2024)
Abstract Background The Danish Health Authority recommended the implementation of new types of emergency departments. Organizational changes in the hospital sector challenged the role, identity, and autonomy of medical specialists. They tend to identify with their specialty, which can challenge successful implementation of change. However, investigations on specialty identity are rare in implementation science, and how the co-existence of different specialty identities influences the implementation of new emergency departments needs to be explored for the development of tailored implementation strategies. The aim of this study was to examine how medical specialty identity influences collaboration between physicians when implementing a new emergency department in Denmark. Methods Qualitative methods in the form of participants' observations at 13 oilcloth sessions (a micro-simulation method) were conducted followed up by 53 individual semi-structured interviews with participants from the oilcloth sessions. Out of the 53 interviews, 26 were conducted with specialists. Data from their interviews are included in this study. Data were analysed deductively inspired by Social Identity Theory. Results The analysis yielded three overarching themes: [1] ongoing creation and re-creation of specialty identity through boundary drawing; [2] social categorization and power relations; and [3] the patient as a boundary object. Conclusions Specialty identity is an important determinant of collaboration among physicians when implementing a new emergency department. Specialty identity involves social categorization, which entails ongoing creation and re-creation of boundary drawing and exercising of power among the physicians. In some situations, the patient became a positive boundary object, increasing the possibility for a successful collaboration and supporting successful implementation, but direct expressions of boundaries and mistrust were evident. Both were manifested through a dominating power expressed through social categorization in the form of in- and out-groups and in an "us and them" discourse, which created distance and separation among physicians from different specialties. This distancing and separation became a barrier to the implementation of the new emergency department.